N26 Help-seeking experiences of patients with Inflammatory Bowel Disease from healthcare professionals: A qualitative descriptive study. (30th January 2023) - Byron, C; Lehane, E; Burton, A; Cornally, N
Abstract: Background: Due to the chronic, relapsing and remitting disease course associated with Inflammatory Bowel Disease (IBD), self-management tools inclusive of conceptualising the problem, acknowledging the need for external help and knowing where to seek help from are essential for the management of IBD. Those living with IBD are challenged by physical symptoms and psychological and social issues that they are unable to self-solve. Help-seeking behaviour (HSB) is a relatively new concept to health services research (Cornally & McCarthy, 2011) and has been infrequently applied to the area of IBD. When IBD-related challenges are beyond self-resolution, patients require help and support from healthcare professionals (HCPs). This engagement must be facilitated at the point of issue recognition, as opposed to at crisis point. Given the dearth of research in this area, this study explored the help-seeking experiences of patients living with IBD for the challenges associated with IBD from HCPs, to enable us through understanding their experiences, how best to support help-seeking pathways and/or early interventions to assist those living with IBD to resolve issues that challenge their day-to-day lives. Methods: A qualitative descriptive design (Sandelowski 2000; Neegaard et al ., 2009; Sandelowski 2010) was employed as little is known regarding the help-seeking experiences of those living with IBD, their sources of help and preferred methods of seeking help. Participants were recruited purposefully from two public university hospitals in the Republic of Ireland that provide dedicated in- and out-patient care to those living with IBD. Data were collected via semi-structured one-to-one phone interviews (n=8). Results: An overarching theme of 'coming to terms with managing my IBD' and four themes of 'help-seeking trigger', 'help-seeking hesitancy', 'help-seeking decision pathway' and 'need for support' emerged from the data by way of latent pattern content analysis. Conclusion: Typically, help is sought for IBD related challenges by contacting their designated IBD nurse directly via text, the preferred method, or via phone. The majority of participants spoke of negative experiences of seeking help prior to the introduction of an IBD nurse. These may be categorised either by lack of service provision or by symptoms being dismissed or not understood by HCPs who lack expertise in the area of IBD. Triggers for seeking help are in line with the challenges identified in our earlier meta-synthesis of patients' experiences of IBD (Byron et al. 2020) and tend to mainly be related to the physical symptoms associated with IBD as well as the medical treatments being delivered. The need for both formal and informal psychological support was identified by participants.